Innovative Education Strategies for Enhancing Digital Literacy and Student Intelligence - Aida Amalliah; Maretta Sihombing; Cut Salsabila Murki Habibi; Joharis Joharis (International Journal of Educational Evaluation and Policy Analysis, 2025)
This study examines the digital literacy of university students in the context of Indonesia's evolving digital landscape. In the era of Industry 4.0 and the emerging Society 5.0, higher education faces the challenge of preparing students not only academically but also as responsible digital citizens. The research explores the level of digital literacy among students, identifies factors contributing to their limited ability to critically evaluate digital information, and proposes strategies to enhance digital skills. Utilizing a quantitative approach with an online questionnaire distributed to students from various higher education institutions, the study assesses competencies in technical usage, information evaluation, and digital ethics. The findings reveal that while a majority of students exhibit basic digital awareness and a tendency to verify information through credible sources, significant gaps remain in their ability to discern misinformation and protect personal data. The study recommends integrating digital literacy into academic curricula, increasing access to reliable digital resources, and conducting regular training workshops. These measures aim to foster a more critical, informed, and digitally secure student body, better equipped to navigate the challenges of the modern information age.